2003
DOI: 10.1097/00043426-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Results in Neuroblastoma Screening: The Parents' View

Abstract: Investigators should be aware of the psychological consequences of hospital admission for tumor screening in children. In ongoing neuroblastoma screening studies, laboratory methods as well as cutoff limits should be selected carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, research that evaluated parents of infants with false out-of-range results has suggested that 5% to 20% of these parents will persist in their concerns about the health of their children for months or years after screening. [5][6][7][8][9] Therefore, PCPs should not take the event of a false out-of-range result too lightly and may wish to discuss this issue with parents on subsequent visits to provide additional reassurance and eliminate any misconceptions.…”
Section: Document False Out-of-range Results and Reassure Parentsmentioning
confidence: 99%
“…However, research that evaluated parents of infants with false out-of-range results has suggested that 5% to 20% of these parents will persist in their concerns about the health of their children for months or years after screening. [5][6][7][8][9] Therefore, PCPs should not take the event of a false out-of-range result too lightly and may wish to discuss this issue with parents on subsequent visits to provide additional reassurance and eliminate any misconceptions.…”
Section: Document False Out-of-range Results and Reassure Parentsmentioning
confidence: 99%
“…368 For other newborns, in whom a positive screening result is later discovered to be false, parental anxiety may also last well into the preschool years. 369 Although children may successfully regain normality after surgery, it is more likely that long periods of follow-up will define them as unwell for a large part of childhood. In addition, all future pregnancies in the family are within doubt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…398 Anxiety during the screening process or experience of a false positive result does not decrease a parent's willingness to undertake screening of subsequent children. 357,358,363,368,369,373,375 However, lower support for screening is shown by parents who have experienced delay between screening and final diagnosis on a previous occasion, 385 who do not feel they were fully informed about the screening process 370,374 or whose children have been found to have a minor problems for which no intervention is needed. 358 Screening is less likely to be declined when it is offered in person or as an adjunct to routine care.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations